ANALYSIS OF VITAMIN C CONTENT AND ANTIOXIDANT ACTIVITY OF GREEN COCONUT (Cocos nucifera L) USING THE DPPH METHOD: ANALISIS VITAMIN C DAN AKTIVITAS ANTIOKSIDANT PADA KELAPA HIJAU (Cocos nucifera L) MENGGUNAKAN METODE DPPH - Baihaqi; Fatahu; Ika Rezvani; Sri Agustina; Sakir (PT. ROCE WISDOM ACEH, 2026)
Green coconut (Cocos nucifera L.) is one of the tropical horticultural commodities widely consumed by Indonesian people and is empirically believed to have health benefits due to its vitamin C and antioxidant compounds. This study aims to analyze the levels of vitamin C and antioxidant activity in water and green coconut meat using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. Vitamin C levels were determined using the iodimetric titration method, while antioxidant activity was measured based on the percentage inhibition of DPPH radicals at five concentration series (1,000-5,000 ppm) using a UV-Vis spectrophotometer, then expressed as an IC50 value through a linear regression equation. The results showed that the average vitamin C levels in coconut water were 29.35 ± 5.08 mg/100 g and in coconut meat were 28.48 ± 4.93 mg/100 g. The IC50 value of coconut water was 5,824.52 ppm and coconut meat was 5,423.78 ppm, both well above the 200 ppm threshold, so both samples were classified as having very weak antioxidant activity based on the DPPH test. Coconut meat showed a slightly lower IC50 than coconut water, but the difference was not substantial. The low levels of vitamin C in both parts of the green coconut fruit are suspected to be one of the main factors in the weak antioxidant activity detected. This study provides baseline data on the antioxidant potential of fresh green coconut without further extraction treatment, which can be a reference for future research on the processing or fortification of coconut-based food products.